Neoliberalism, postmodernity, and the contemporary memorial-building boom - Clewer, Nicola (Rowman & Littlefield, 2022)
"Clewer explores the various ways the sublime is manifest in contemporary memorial architecture as well as its philosophical and political implications. She shows how the national monument is being transformed at a time when the nation-state and national identity are under extreme scrutiny"--